FIRST REPORT OF DIGENEANS: CLINOSTOMIDAE METACERCARIA INFECTING PIRAPITINGA IN THE STATE OF ACRE, BRASIL - Ribeiro, Paula de Lacerda Santos; Picolo, Isabela Cristina; Nascimento, Williane Silva do; Moura, Matheus Calixto; Dantas, Junio Roney Lima; Santos, Francisco Glauco de Araújo; Meneguetti, Dionatas Ulises de Oliveira; Vieira, Lisandro Juno Soares (South American Journal of Basic Education, Technical and Technological, 2018)
This article presents the first report of Clinostomum sp. infecting Piaractus brachypomus in Acre. Specimens of Clinostomum sp. were identified in fish cultured in fish farming in the rural municipality of Bujari, Acre. This was the first report of Piaractus brachypomus as secondary host of Clinostomum sp. in the state of Acre, being another parasite with zoonotic potential in it. A greater extent of occurrence of Clinostomum sp. in Brazil was verified.